Example or alter ego ? aspects of the portrait historié in Western art from antiquity to the present - Manuth, Volker 1956-; Leeuwen, Rudie van 1981-; Koldeweij, A. M. 1953- (Nijmegen art historical studies, 2016)
The present collection of essays on the subject of the portrait historié treats examples of this subgenre of portraiture stemming from Classical Antiquity, medieval times, the Renaissance and Baroque period, but also from Romantic era and the modern movements of the nineteenth and twentieth centuries. A portrait historié can be described as an artistic rendering of an individual in the guise of a historical figure. In a broader and more modern sense it can be understood as a representation or figuration of the self which appropriates and incorporates visual metaphors by means of allegorisation and identification. This book is the result of a research project of the Art History Department in collaboration with the Archaeology Department of the Faculty of Arts of the Radboud University Nijmegen